PROSES PERENCANAAN PEMBANGUNAN DENGAN PENDEKATAN PARTISIPATIF DI KECAMATAN TEMBALANG KOTA SEMA - Winarendra Imam Prakoso; Ari Subowo (Journal of Public Policy and Management Review, 2019)
The process of development planning based on participatory it’s very important for the sustainability and success of a development. Tembalang Subdistrict as one of the Subdistricts which has very large area with a geographical location on the border and very large population which has an average level of low education becomes a problem. The main purpose of this research to describe or visual in detail and depth about the stages of development planning and to know what its the factors has influence the community participation in development planning in Tembalang Subdistrict, Semarang City based on Abe Alexander's 6 planning stages and 4 characteristics of participatory planning according to Wicaksono & Sigiarto . The method used in this research is a qualitative descriptive with data collection techniques used semi-structured interviews and non-participant observation and data analysis technique uses an interactive model analysis from Miles and Huberman which includes the stages of reduction, presentation and data verification. The results of this research show that in the process of development planning stages have not been implemented optimally, community participation in following the development planning process was still relatively low, there are problems related to the preparation of development planning deliberations that have not involved elements of society in general; lack of understanding of the community in determining the priority scale; distrust and openness from elites of the District and Urban Village to community proposals; and lack of time for organizing musrenbang. The recommendations generated from this research are; The Government should more active in disseminating development planning; Increase trust in community proposals; the holding of the discussion of carrying capacity in the form of potential and the addition of time to organize development planning deliberations